Illicit financial flows from South Africa : decolonial perspectives on political economy and corruption - Kamga, Serges Djoyou (Serges Alain Djoyou) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book examines the detrimental impact of illicit financial flows on South Africa's development, political economy and transformation in the twenty-first century. Over the years, illicit financial flows have led to the systematic looting and channelling away of South African resources, yet it is rarely studied by researchers looking to explain the country's underdevelopment and political economy. This book looks across sectors, showing that illicit financial flows cut across all the key pillars of development, frustrating the betterment of peoples' lives in South Africa. Investigating the problem from a decolonial perspective, the book delves deep into the catastrophic impacts of illicit financial flows for people and the economy, discusses how the problem is being combatted, and ultimately suggests solutions for rebuilding social trust between people and the state. Making an important contribution to the decolonial debate, as well as to discussions of South Africa's political economy, this book will be of interest to researchers across African Studies, Global Development, Political Science, Law and Corruption Studies"--
Insights into Illicit Financial Flows from South Africa / Gerard Emmanuel Kamdem Kamga -- Nexus Between Illicit Financial Flows, Governance and Development in the Republic of South Africa / Sakah Bernard Nsaidzedze and Pacific Thales Yapatake Kossele -- Social and Economic Effects of Illicit Financial Flows in South Africa / Moorosi Leshoele and Vusi Gumede -- Illicit Trading in the Mining Sector: A Threat to South Africa's Industrial Development / Asanda Fotoyi -- Under the Radar Illicit Outflows from South Africa: Effects and Solutions / Asteria Nsamba and George Nsamba -- Illicit Financial Flows and the Marginalised Population: A Case of People with Disabilities in South Africa / Sindile A Ngubane-Mokiwa -- The Political Economy of Tobacco Illicit Trade in South Africa / Toendepi Shonhe -- The Civil Society and the Fight Against Illicit Financial Flows in Africa: The Case Study of OUTA and the "State Capture" in South Africa / Marianne SeÌverin -- An Institutional and Public Policy Response to Illicit Financial Flows in the Mining Industry of Southern Africa: The Case of Namibia and South Africa / Tk Pooe -- Regional Economic Communities and the Fight Against Corruption in Africa: An Analysis of the Roles of the Southern African Development Community / Samuel Ojo Oloruntoba -- Illicit Financial Flows in South Africa: An Examination in the Light of "the 1884 Scramble for Africa' / Serges Djoyou Kamga -- Illicit Financial Flows in (South) Africa and the Problem of Meaning / Isaac Shai -- Nailing the Devil on The Cross: South Africa's Responses to the Illicit Financial Flows Scandal / Siphamandla Zondi -- The Nexus Between Illicit Financial Flows and the Recent Downgrade of South Africa's Ratings by Credit Ratings Agencies / Gerard Emmanuel Kamdem Kamga and Serges Djoyou Kamga -- Reactive Versus Constructive Agency in Combating Illicit Financial Flows from a South African Perspective / Paul Tembe -- The Ethics of Power, Illicit Financial Flows and the Right to Development: A Reflection on South Africa / Mofihli Teleki -- Illicit Financial Flows, State Capture and the Right to Development in South Africa / Serges Djoyou Kamga.
OCLC-licensed vendor bibliographic record.
Keywords: Flow of funds -- Corrupt practices -- South Africa; Finance -- Corrupt practices -- South Africa; Capital movements -- South Africa; Corruption -- South Africa